A new species of the diogenid hermit crab genus Pseudopaguristes McLaughlin, 2002 from the Northern Mariana Islands, Micronesia - Komai, Tomoyuki; Miller, Allison K.; Malay, Maria Celia D. (Zootaxa, 2022)
The diogenid hermit crab genus Pseudopaguristes McLaughlin, 2002 is currently represented by 15 species worldwide. In this study, we describe a new species of the genus, P. flavioculus, based on a unique male holotype from off Sarigan, Northern Mariana Islands, Micronesia, at depth of 131–133 m. The new species appears similar to the type species of the genus, P. janetkae McLaughlin, 2002, but the lack of conspicuous spines on the dorsal face of the right cheliped carpus, the possession of a median row of tiny spines on the dorsal face of the left cheliped carpus, and different colour pattern of the cephalic appendages and the ambulatory legs distinguish P. flavioculus n. sp. from P. janetkae. Pseudopaguristes has been differentiated from the two allied genera, Paguristes Dana, 1851 and Areopaguristes Rahayu, 2012, by the possession of eight functional pairs of gills (versus 13 pairs in Paguristes and 12 pairs in Areopaguristes), but our examination of the new species and three other congeneric species available for study clarifies that the development of arthrobranchs on the maxillipeds 3 and chelipeds is rather variable in species currently assigned to Pseudopaguristes. Careful observation of the anterior arthrobranchs is recommended to avoid misinterpretation in the counts of gill numbers.